Modified High-Fat High-Sucrose Diet Promotes Obesity and Alters Colonic Cytokines - Bernadette Dian Novita; I Gede Putu Adhi Wedharga; Yudy Tjahjono; Hendy Wijaya; Imelda Theodora; Martha Ervina; Yufita Ratnasari Wilianto; Sianty Dewi; Irene Lingkan Parengkuan; Herjunianto Herjunianto; Sabrina Maria Ghasani; Michael Christian Limantoro; Ferdinand Wiliam Jaya (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Western dietary patterns are often associated with increasing non-communicable diseases, including inflammatory bowel disease (IBD). In experimental models, a high-fat high-sucrose (HFHS) diet is used to mimic metabolic and inflammatory effects of such diets, however the data regarding colonic inflammation in Indonesia remain limited. Therefore, this study was conducted evaluated the impact of HFHS feeding on colonic interleukin (IL)-6, IL-10 expression, and the IL-6/IL-10 ratio.METHODS: Six weeks old male C57BL/6 mice were randomly assigned to a normal fat diet (NFD) or HFHS diet group and fed ad libitum for 8 weeks. Colonic tissues were collected, and IL-6 and IL-10 expression was analyzed by immunohistochemistry.RESULTS: HFHS-fed mice showed significant increases in body weight (increased by 22.44%, p=0.0047) and caloric intake (increased by 125.17%, p=0.0000), confirming obesity induction. Colitis was also evident, with higher histological colitis scores (p=0.0072). However, colonic IL-6 (increased by 9.12%, p=0.1236), IL-10 (increased by 1.49%, p=0.8013), and the IL-6/IL-10 ratio (increased by 7.38%, p=0.4000) showed no significant differences compared to NFD.CONCLUSION: In C57BL/6 mice, an 8-week modified HFHS diet induced obesity, increased caloric intake, and mucosal injury, but did not significantly alter colonic IL-6, IL-10, or their ratio. This suggests preserved mucosal immune homeostasis consistent with an early compensatory phase rather than overt cytokine-driven inflammation. Longer or more intensive exposure may disrupt this balance, highlighting the need for further studies to define the temporal threshold and clarify immune microbiome interactions in colitis progression.KEYWORDS: high-fat high-sucrose diet, colon inflammation, IL-6, IL-10, obesity mice